1993
DOI: 10.1172/jci116441
|View full text |Cite
|
Sign up to set email alerts
|

Genetic basis for a lower prevalence of deficient CYP2D6 oxidative drug metabolism phenotypes in black Americans.

Abstract: Debrisoquin hydroxylase (CYP2D6) is a cytochrome P450 enzyme that catalyzes the metabolism of > 30 commonly prescribed medications. Deficiency in CYP2D6 activity, inherited as an autosomal recessive trait, was found to be significantly less common in American blacks (1.9%) than whites (7.7%). To determine the genetic basis for this difference, inactivating CYP2D6 mutations were assessed by allele-specific PCR amplification and RFLP analyses of genomic DNA from 126 unrelated whites and 127 unrelated blacks. Bla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
2

Year Published

1997
1997
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(39 citation statements)
references
References 28 publications
0
37
2
Order By: Relevance
“…When combined with previously published methods to detect CYP2D6*5 alleles (that are not compatible with multiplexing), this approach can identify ϳ90% of individuals in Western European populations with PM phenotype [39]. CYP2D6*4 is also found at relatively high frequencies in several non-European populations: 8.3% in Canadian Inuit [40], 8.5% in African Americans [41], and 11.3% in Turks [42]. Due to the low incidence of defective alleles in Africans and Oriental Asians, PM phenotypes are rare in these populations compared with Western Europeans [43].…”
Section: Resultsmentioning
confidence: 99%
“…When combined with previously published methods to detect CYP2D6*5 alleles (that are not compatible with multiplexing), this approach can identify ϳ90% of individuals in Western European populations with PM phenotype [39]. CYP2D6*4 is also found at relatively high frequencies in several non-European populations: 8.3% in Canadian Inuit [40], 8.5% in African Americans [41], and 11.3% in Turks [42]. Due to the low incidence of defective alleles in Africans and Oriental Asians, PM phenotypes are rare in these populations compared with Western Europeans [43].…”
Section: Resultsmentioning
confidence: 99%
“…Ziegler et al, (1977) observed that nortriptyline concentrations were nearly 50% higher in African-Americans than Whites (113.5 vs.75.7 ng/mL). The potential genetic basis for ethnic differences in PNCs likely relates to differences in the frequency of defective CPY2D6 alleles (i.e., so-called "poor metabolizers"), with a higher rate of defective alleles for this enzyme generally, but not always, observed in Asians and those of African ancestry [30][31][32][33][34][35]. For a given dose of nortriptyline, higher plasma concentrations of the drug will be achieved due to slower metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…The metabolism by aromatic hydroxylation in humans is subject to the CYP2D6-dependent genetic oxidative polymorphism [6]. The patients deficient with CYP2D6 enzyme activity (2% of African-Americans, 2% of Asians, 7% of Caucasians) are considered poor metabolizers of NBL [7][8]. The absolute oral bioavailability of NBL is 12% in extensive metabolizers and 96% in poor metabolizers with the mean terminal half-life of approximately 10 h [9].…”
Section: Introductionmentioning
confidence: 99%